Evaluation of the performance of local, Rhode Island red (RIR) and Fayoumi breeds of chicken under different management regimes in the highlands of Ethiopia - Dana, N. (Swedish University of Agricultural Sciences, 1999)
This thesis presents studies conducted under farm and research station conditions to evaluate the comparative performance of local and exotic genotypes of chicken under different feeding and management regimes. Paper I reports the findings of a study conducted under research station conditions to evaluate the effect of choice feeding of energy and protein feeds on the performance of RIR and Fayoumi breeds of Chicken. The birds were subjected to three dietary/management regimes. These were: 1) birds offered a single complete diet (layer mash) and remaining in confinement, 2) birds given free choice maize and noug cake and remaining in confinement and, 3) birds given free choice maize and noug cake and allowed to scavenging for about six hours during the day time. Analysis of the performance data indicated that birds receiving a single complete diet had a higher daily feed intake and conversion efficiency compared to the choice fed hens. Choice feeding, whether or not accompanied by scavenging, resulted in poorer performance in all egg production parameters measured. The total number of eggs/bird over the experimental period, hen-day and hen-housed egg productions and total egg mass were on average 78,44.6%, 43.3% and 22.7kg, respectively for birds given a single complete diet, while the corresponding figures for choice fed chickens both under confinement and scavenging were at least 30% lower. Egg production performance and mortality did not vary between the breeds; while the highest mortality was recorded in choice fed hens allowed to scavenging (19%), followed by the choice fed and confined group (8%). RIR birds had a heavier slaughter weight (1,575g) and dressed weight (973g) than the Fayoumi (1,078 and 633g, respectively), while dressing percentage was similar for all breeds and dietary regimes. Choice feeding significantly increased abdominal fat deposition, with the highest being recorded in those birds remaining in confinement (63g). Abdominal fat deposition was significantly higher in the RIR breed. Paper II reports the results of a trail undertaken to evaluate the egg production potential of scavenging RIR and local birds supplemented with 60% g/bird/day of equal proportions of a maize and noug cake mixture, under village conditions. One hundred and fifty pullets of each breed, allocated to 15 households were evaluated for six months. Supplementation significantly improved productivity of both local and RIR birds. Total egg production per hen increased from 36 to 45 average hen-housed egg production from 26 to 32% and average hen-day egg production from 38 to 45%, while mortality was reduced slightly from 30 to 27.5% with supplementation. The RIR breed had a superior performance in all egg production parameters measured, including egg weight, with slightly lower mortality (28%) than the local chicken (30%). Local birds laid smaller eggs but with thicker shells compared to the RIR while yolk colour was found to be similar.